-2c+12=2c-6+6c-12

Simple and best practice solution for -2c+12=2c-6+6c-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2c+12=2c-6+6c-12 equation:


Simplifying
-2c + 12 = 2c + -6 + 6c + -12

Reorder the terms:
12 + -2c = 2c + -6 + 6c + -12

Reorder the terms:
12 + -2c = -6 + -12 + 2c + 6c

Combine like terms: -6 + -12 = -18
12 + -2c = -18 + 2c + 6c

Combine like terms: 2c + 6c = 8c
12 + -2c = -18 + 8c

Solving
12 + -2c = -18 + 8c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-8c' to each side of the equation.
12 + -2c + -8c = -18 + 8c + -8c

Combine like terms: -2c + -8c = -10c
12 + -10c = -18 + 8c + -8c

Combine like terms: 8c + -8c = 0
12 + -10c = -18 + 0
12 + -10c = -18

Add '-12' to each side of the equation.
12 + -12 + -10c = -18 + -12

Combine like terms: 12 + -12 = 0
0 + -10c = -18 + -12
-10c = -18 + -12

Combine like terms: -18 + -12 = -30
-10c = -30

Divide each side by '-10'.
c = 3

Simplifying
c = 3

See similar equations:

| -6x+8=14-3x | | b+b+b+6=6b+5-2b+9 | | y^2+7y-30=0 | | 4x-2=-2x-56 | | 7x-10=-37-2x | | 8k-6+3k-2k+3=4*33 | | 6-5x-2x=34 | | 6w^2+33w-18= | | 2d-8-5d=-3d-2d+6 | | 15=3.4n-2(n-4) | | (3x)+(4x-24)=180 | | x^2+1045x+14278=0 | | P=100-0.5q | | 3c-6+2c=10c-2c+6 | | 5u+6v-3(3u-2v)= | | 2n-4m=8 | | 12s^2-13st-4t^2= | | 15x-10=-9x+12 | | 10x+1=2x+5 | | 41-8x=-6x-23, | | 3(3x+4)-2-5-7x=20 | | -7q+8-6+5q=8 | | 3x+16=12x-74 | | -r+7r-3+5r=93 | | w=mt+b | | =2(3s-8)+7 | | -(4x-4)-(-2x-6)+3=-3(x-1)-(6x+2)+3 | | 2b-10b-15+5=8b-40-4b-6 | | 10x^4-21x^2+9= | | 6a+3a=18 | | 3x+14+2x+1=180 | | 11a-4a-18=2a+a+10 |

Equations solver categories